Transient stability improvement based on out-of-step prediction - Sobbouhi, Ali Reza; Vahedi, Abolfazl (Electric power systems research, 2021)
•Introducing a novel concept for transient stability improvement by using out-of-step prediction.•Activating stability improvement depends on the remaining time until instability.•Reducing the imposed transients on power system and synchronous generator.•Introducing a new and simple algorithm based on “speed deviation-derivative of speed” plane. In this paper, a novel concept for transient stability improvement is introduced by using out-of-step prediction. Unlike conventional improving stability methods, which are always online, this concept makes activation of the stabilization process subject to the prediction. Firstly, the method utilizes a prediction algorithm to predict the stability of a synchronous generator and consequently, if adequate time remains, activates a method for improvement of stability. This concept reduces the imposed transients on power system and hence the probable damage on the synchronous generator. The proposed philosophy is adapted for single or several prediction methods. Additionally, to confirm the effectiveness of this approach, a new and simple algorithm for instability assessment is introduced which maps the generator transient behavior on the “speed deviation-derivative of speed” plane where the trend of this curve is employed for instability prediction by tangent line. The proposed concept and prediction method are validated on IEEE 39 bus test system. The results demonstrate the introduced approach is quite effective. The simulations and algorithm implementation are carried out using Power Factory® and MATLAB software, respectively.